Lipophilicity predicts the ability of nonsulphonylurea drugs to block pancreatic beta-cell KATP channels and stimulate insulin secretion: statins as a test case - Real, Joana; Miranda, Caroline; Olofsson, Charlotta S.; Smith, Paul A. (Wiley, 2018)
Aims